Produção de nanopartículas de curcumina com policaprolactona (PCL) e avaliação da nanotoxicidade em Drosophila melanogaster - Borsato, Patrícia Aparecida Macário (2020)
Curcumin, an orange-yellow pigment isolated from Curcuma longa rhizome, has biological and pharmacological properties with therapeutic potential in the treatment of various chronic diseases, as well as antioxidant and anti-inflammatory activity. However, curcumin has technological barriers that limit its application such as low solubility and low bioavailability. In this context, nanotechnology-based approaches are gaining attention due to their potential to alter / improve the in vitro and in vivo effects of curcumin. However, so far little is known regarding the toxicity of curcumin-containing nanoparticles in animal models. For this, Drosophila melanogaster, recognized as an alternative test organism, has been used to evaluate the toxicity or benefit of bioactive compounds. Thus, the objective of this work was to produce polycaprolactone encapsulated curcumin nanoparticles (PCL) and to evaluate its toxicity using the fruit fly (Drosophila melanogaster) as an alternative biological model. The nanoparticles were characterized by Differential Scanning Calorimetry (DSC), Infrared Spectrophotometry (FTIR), Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD) and Dynamic Light Scattering (DLS) analyzes. Spherical nanoparticles with mean diameter equal to 215 ± 2 nm were obtained according to DLS analysis and corroborated by microscopy images. In the curcumin FTIR spectrum it was possible to identify the absorption bands that are generally used to identify this compound, which was not identified in the curcumincontaining nanoparticle sample. The curcumin melting peak was also not observed in the nanoparticles, and the crystalline melting temperature of the PCL was not changed when compared to the curcumin-free nanoparticles. In vivo results using Drosophila melanogaster demonstrated that nanoparticles containing curcumin showed a significant mortality rate only at the highest dose (100 µM) evaluated, treatment using free curcumin had no effect on mortality. Change in the locomotor performance of the flies was observed from the dose of 30µM for both treatments. In ex vivo tests, there was a significant inhibition of AChE and BChE activity, both at 100µM. Catalase activity was influenced both in the treatment with nanoparticles containing curcumin and for free curcumin from 10µM. Total thiols showed a significant difference in relation to the control at 30 and 100µM for nanoparticles containing curcumin, and at 30µM for free curcumin. Non-protein thiols, no significant difference was observed for any of the treatments. The results indicate that it was possible to encapsulate curcumin in the polymeric matrix of polycaprolactone, as well as suggest a low nanotoxicity using an alternative biological model.